2005
DOI: 10.1111/j.1600-0579.2004.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Predoctoral implant dentistry curriculum survey: European dental schools

Abstract: Predoctoral implant dentistry educational programmes vary from school to school. Yet a large percentage of schools agree on certain topics, including the importance of including implant education in predoctoral dental programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 19 publications
6
54
0
1
Order By: Relevance
“…However, it is a matter of discussion whether we can include more basics with theoretical and practical aspects of dental implant at an undergraduate level in their curriculum as recommendation made by various authors in the literature. [13][14][15][16][17] In order to prepare students to practice dental implants into their private practice, dental colleges need to incorporate a combination of clinical and laboratory trainings in dental implants at undergraduate programs. A further study of a broader population of GDPs would be beneficial and may contribute to dental implant education, practice and regulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is a matter of discussion whether we can include more basics with theoretical and practical aspects of dental implant at an undergraduate level in their curriculum as recommendation made by various authors in the literature. [13][14][15][16][17] In order to prepare students to practice dental implants into their private practice, dental colleges need to incorporate a combination of clinical and laboratory trainings in dental implants at undergraduate programs. A further study of a broader population of GDPs would be beneficial and may contribute to dental implant education, practice and regulation.…”
Section: Discussionmentioning
confidence: 99%
“…5 A survey of European dental schools completed in 2002 indicated that 75% of responding schools had established implant dentistry programmes, but only 37% reported that their undergraduate students gained clinical experience in the restoration of implant cases. 7 Studies conducted in the United States have revealed that 20% of predoctoral (undergraduate) programmes have included implant dentistry in their curriculum since the 1970s. 8 In the…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there is a dearth in the literature regarding postgraduate dental implant education, [1][2][3] coincidentally there is also a dearth in the literature as regards predoctoral (undergraduate) dental implant education. 4,5 It is for this reason, we utilized our systematic approach (Fig. 1) for postgraduate dental implant education in Ibadan, Nigeria, West Africa to introduce and develop the undergraduate dental implant curriculum and education in West Africa.…”
Section: Discussionmentioning
confidence: 99%